Rothmund-Thomson Syndrome: Insights from New Patients on the Genetic Variability Underpinning Clinical Presentation and Cancer Outcome - ELÇİOĞLU, HURİYE NURSEL (MDPI, 2018)
Biallelic mutations in RECQL4 gene, a caretaker of the genome, cause Rothmund-Thomson type-II syndrome (RTS-II) and confer increased cancer risk if they damage the helicase domain. We describe five families exemplifying clinical and allelic heterogeneity of RTS-II, and report the effect of pathogenic RECQL4 variants by in silico predictions and transcripts analyses. Complete phenotype of patients #39 and #42 whose affected siblings developed osteosarcoma correlates with their c.[1048_1049del], c.[1878+32_1878+55del] and c.[1568G>C; 1573delT], c.[3021_3022del] variants which damage the helicase domain. Literature survey highlights enrichment of these variants affecting the helicase domain in patients with cancer outcome raising the issue of strict oncological surveillance. Conversely, patients #29 and #19 have a mild phenotype and carry, respectively, the unreported homozygous c. 3265G>T and c. 3054A>G variants, both sparing the helicase domain. Finally, despite matching several criteria for RTS clinical diagnosis, patient #38 is heterozygous for c. 2412_2414del; no pathogenic CNVs out of those evidenced by high-resolution CGH-array, emerged as contributors to her phenotype.
Keywords: Rothmund-Thomson syndrome; RECQL4; clinical expressivity; transcript analysis; osteosarcoma outcome; BALLER-GEROLD-SYNDROME; RECQL4 MUTATIONS; DAMAGE REPAIR; VARIANTS; OSTEOSARCOMA; HELICASE; DISEASES; LOCALIZATION; ASSOCIATION; PREDICTION